N-Truncated Aβ Starting at Position Four—Biochemical Features, Preclinical Models, and Potential as Drug Target in Alzheimer’s Disease - Bayer, Thomas A. (Frontiers in Aging Neuroscience, 2021)
The discussion whether amyloid plaque A is a valid drug target to fight Alzheimer’s disease (AD) has been a matter of scientific disputes since decades. This question can only be settled by successful clinical trials and the approval of disease-modifying drugs. Many clinical trials with antibodies against different regions of the amyloid A peptide were discontinued, as they did not met their clinical endpoints. Recently, passive immunization of AD patients with Donanemab, an antibody directed against the N-terminus of pyroglutamate A, showed beneficial effects in a phase II trial supporting the concept that N-truncated A is a relevant target for AD therapy. There is long-standing evidence that N-truncated A variants are, besides full-length A1-42, the main variants found in amyloid plaques, therefore their role in triggering AD pathology and as targets for drug development are of interest. While the contribution of pyroglutamate A3-42 to AD pathology has been well studied in the past, the potential role of A4-42 has been largely neglected. The present review will therefore focus on A4-42 as a possible drug target on the basis of human and mouse pathology, in vitro and in vivo toxicity and anti-A4-X therapeutic effects in preclinical models.